GE_GERICHTE P/17631/2019 vom 6. Juli 2020 - GE Cour de justice (2020)
PLAINTE PÉNALE;MAGASIN;VIOLATION DE DOMICILE;NE BIS IN IDEM;CONCOURS RÉEL;EXPULSION(DROIT PÉNAL);IMPUTATION | CP.30.al1; CP.186; CP.51; CP.66abis